2019
DOI: 10.1172/jci129195
|View full text |Cite
|
Sign up to set email alerts
|

CNS-targeting pharmacological interventions for the metabolic syndrome

Abstract: Conflict of interest: RDD is currently an employee of Novo Nordisk. RDD is a cofounder of Marcadia, a company that pioneered the discovery of glucagon mixed agonists. It was acquired by Roche and later Novo Nordisk. He is a coinventor on multiple patents owned by Indiana University. MHT is a scientific advisor for Erx Biotech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 200 publications
0
17
0
1
Order By: Relevance
“…New pharmacological tools that selectively and safely target hypothalamic neuronal circuits affected by obesity are on the horizon [ 38 , 104 ]. However, the cellular and molecular mechanisms leading to hypothalamic neurons’ dysfunction in obesity have only begun to emerge, and additional research will be needed before functional optimization and clinical translation of these brain-directed agents.…”
Section: Discussionmentioning
confidence: 99%
“…New pharmacological tools that selectively and safely target hypothalamic neuronal circuits affected by obesity are on the horizon [ 38 , 104 ]. However, the cellular and molecular mechanisms leading to hypothalamic neurons’ dysfunction in obesity have only begun to emerge, and additional research will be needed before functional optimization and clinical translation of these brain-directed agents.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated release of monoamines promotes satiety and reduces feeding through the activation of postsynaptic α-and β-adrenergic receptors and D1/D2 receptors. 21 The d-isomer of amphetamine is more potent than its I-isomer. 22 It has an extensive distribution in most of the tissues and possesses a potent psycho-stimulant effect.…”
Section: Current Approaches For Management Of Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Hypertension and cardiac arrhythmias can occur at higher doses, but they tend to resolve after dose reduction. 21,35 A study by Williams et al showed that dexamphetamine has been a less commonly abused drug compared to abuse of other substances. 35 Apart from this, dexamphetamine can lead to some clinically significant drug interactions with drugs such monoamine oxidase inhibitors; antacids and other drugs used for peptic ulcers; antipsychotics, such as chlorpromazine and haloperidol; norepinephrine; and anticonvulsants, such as phenytoin and phenobarbital.…”
Section: Potential Safety Concerns Of Dexamphetaminementioning
confidence: 99%
“…Ces deux modifications contribuent à prolonger la durée d'action du peptide, qui est de 8 jours pour le sémaglutide injectable, alors qu'elle n'est que de quelques minutes pour le GLP1 natif. La formulation du sémaglutide pour prise orale associe le peptide le N-[8 (2-hydroxylbenzoyl) amino] hormones [8]. Des agonistes spécifiques des récepteurs du GLP1 (aGLP1) ont également été développés, ainsi que des inhibiteurs de la dipeptidyl peptidase 4 (DPP4), la principale enzyme responsable du catabolisme du GLP1 et du GIP.…”
Section: Le Sémaglutide Administré Par Voie Oraleunclassified